1993
DOI: 10.1002/gcc.2870080311
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of 3p25→pter in a primary follicular thyroid carcinoma and its metastasis

Abstract: We report the cytogenetic analysis of a follicular thyroid carcinoma and its bone metastasis. Both lesions had identical chromosomal abnormalities, with a der(3)t(2;3)(q13;p25) as the most likely primary clonal alteration. Our findings corroborate previous observations of frequent 3p deletions in thyroid follicular carcinomas and suggest that the minimal chromosomal region of loss in these tumors is 3p25-->pter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
3

Year Published

1996
1996
2006
2006

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 8 publications
1
21
3
Order By: Relevance
“…We used four markers at chromosome 3p25-14. LOH was found in 20% of the tumors, but only a single tumor showed LOH at this location and not on chromosome lOq, which is in contrast to earlier reports (Jenkins et al 1990;Herrmann et al 1991;Roque et al 1993). Although small interstitial deletions cannot be excluded, we conclude that LOH on 3p is probably not a prerequisite for development of follicular thyroid carcinomas.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…We used four markers at chromosome 3p25-14. LOH was found in 20% of the tumors, but only a single tumor showed LOH at this location and not on chromosome lOq, which is in contrast to earlier reports (Jenkins et al 1990;Herrmann et al 1991;Roque et al 1993). Although small interstitial deletions cannot be excluded, we conclude that LOH on 3p is probably not a prerequisite for development of follicular thyroid carcinomas.…”
Section: Discussioncontrasting
confidence: 87%
“…Former studies of thyroid tumors have implicated LOH at chromosome Ilql3 in follicular adenomas (Matsuo et al 1991), at chromosome 3p in follicular carcinomas (Herrmann et al 1991;Roque et al 1993), and at chromosome lOq in atypical adenomas and carcinomas (Zedenius et al 1995a). However, the number of carcinomas was small in the latter study.…”
Section: Discussionmentioning
confidence: 67%
“…11-14,24 -26 The short arm of chromosome 3 has been reported to contain rearrangements, and a minimal common deleted region at 3p25-pter has been detected. 14,25 Jenkins et al 12 reported aberrations that were mainly deletions in three follicular carcinomas investigated, and we found a loss of chromosome 22 in 7 of the 13 follicular carcinomas studied. 27 Similarly, only few anaplastic carcinomas with an abnormal karyotype have been described, 12,28 and the molecular mechanisms involved in the genesis of this type of thyroid carcinoma are unknown.…”
mentioning
confidence: 76%
“…This pattern appears different from the single pathway of step-wise genetic progression envisioned for colorectal and pancreatic carcinomas, which nearly all contain APC 10,42,43 or KRAS 44 mutations, respectively. Although PPAR␥ rearrangement and aneuploidy appear to arise independently in early follicular carcinomas, they can co-exist 16,18 (TG Kroll and JA Fletcher, unpublished data). In two such published cases, PPAR␥ rearrangement and aneuploidy appeared together in recurrent 16 and metastatic 18 follicular cancers.…”
Section: Discussionmentioning
confidence: 99%
“…15,[17][18][19]21,22 Recent studies have shown that t(2;3)(q13;p25) forms a PAX8-PPAR␥ gene fusion 21 that is present in a subset of follicular carcinomas. 21,30,31 Here, we used interphase FISH with probes flanking the PPAR␥ gene to investigate these 3p25 rearrangements.…”
Section: Detection Of 3p25/ppar␥ Rearrangement and 3p25 Aneusomymentioning
confidence: 99%